The implications of microsurgical anatomy for surgical approaches to the sellar region - Isolan, Gustavo Rassier; Pires de Aguiar, Paulo Henrique [UNESP]; Laws, Edward R.; Paim Strapasson, Atahualpa Caue; Piltcher, Otavio (Springer, 2009)
The knowledge of the normal anatomy and variations regarding the management of tumors of the sellar region is paramount to perform safe surgical procedures. The sellar region is located in the center of the middle cranial fossa; it contains complex anatomical structures, and is the site of various pathological processes: tumor, vascular, developmental, and neuroendocrine. We review the microsurgical anatomy (microscopic and endoscopic) of this region and discuss the surgical nuances regarding this topic, based on anatomical concepts.
Keywords: Pituitary; Surgical approaches; Anatomy; Tumor